2011
DOI: 10.2174/1876399501103010001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Betaine on Hepatic Fibrosis and Homocysteine in Nonalcoholic Steatohepatitis - A Prospective, Cohort Study

Abstract: Abstract:Introduction: Nonalcoholic steatohepatitis (NASH) is an important cause of cirrhosis and over the past decade has accounted for an increasing proportion of liver transplants in the United States. Unfortunately there is no treatment for NASH except for risk factor modification. The aims of our study were to assess the impact of betaine on liver function tests, homocysteine levels and hepatic fibrosis in a prospective cohort of NASH patients Materials and Methodology: Between July 2003 and June 2006, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In a small pilot study, 1 year of betaine therapy improved AST ( P < 0.02) and ALT ( P < 0.007) as well as the degree of steatosis, necroinflammatory grade, and fibrosis stage 6. In an ongoing study of NASH patients, betaine treatment attenuated ALT concentrations and improved the grades of steatosis, inflammation, and fibrosis 25…”
Section: Discussionmentioning
confidence: 95%
“…In a small pilot study, 1 year of betaine therapy improved AST ( P < 0.02) and ALT ( P < 0.007) as well as the degree of steatosis, necroinflammatory grade, and fibrosis stage 6. In an ongoing study of NASH patients, betaine treatment attenuated ALT concentrations and improved the grades of steatosis, inflammation, and fibrosis 25…”
Section: Discussionmentioning
confidence: 95%
“…It is interesting to note that betaine deficiency as seen in animal models of MAFLD has been correlated with increased disease severity, a similar trend to that seen in patients [ 164 ]. Importantly, betaine treatment decreased the grade of histological steatosis, inflammation, and fibrosis in MAFLD patients [ 165 , 166 ]. Migilo et al reported that oral administration of betaine for 8 weeks to MAFLD patients reduced hepatomegaly and liver-injury-marker enzymes [ 167 ].…”
Section: Disease Prevention By Betaine Administrationmentioning
confidence: 99%
“…In a prospective, cohort study was accomplished for evaluate impact of betaine on liver function tests, homocysteine levels and hepatic fibrosis in NAFLD, conducted by Mukherjee et al 45 , were included 35 patients, but 23 patients completed the study, by to present high liver enzymes and biopsy-proven NAFLD for BRUNT criteria 46 within twelve months of study. Patients used 10 grams/ day of betaine anhydrous for one year.…”
Section: Betainementioning
confidence: 99%